A virtualidade como ferramenta no processo comunicacional e ecossistêmico do Ensino Superior Presencial no curso de Administração do (CIESA) - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In the present project it’s intended to approach virtuality as a communicational and eco systemic tool of in-class Higher Education, in the Adminstration course of Centro Universitário de Ensino Superior (CIESA). The methodology is classified as qualiquantitative, with the use of collection instruments such as questionnaires, interviews and direct observations. In regards to the technical procedures, bibliographic research and field research will be used as the method of case study. As research’s goals, one approached the changes virtuality has caused to in-class Higher Education’s alumni in their learning processes from communicational and eco systemic scope’s matters, besides drawing attention to the guiding questions in this apparently new process for the academic. Concluding this project, we demonstrated that technology has changed by the passing years, through platforms and interfaces created in order to enhance teaching, which interferes directly in the virtualization of the subject’s processes, somehow creating new paradigms and complex questions from a scientific point of view about the eco systemic prism. It was demonstrated what is the responsibility as an institution, teacher and student towards adaptation of those changes, in a way that communication was observed as study object in the complex environment that is the Higher Education’s ambience.
Keywords: Ecossistemas Comunicacionais; Virtualidade; Ensino Superior Presencial; Convergência digital; Educação a Distância (EAD; CIENCIAS SOCIAIS APLICADAS: COMUNICACAO